APPLICATION OF THE PIRFICT MODEL IN THE RIMAS DATABASE - Barbosa, G. L. [UNESP]; Kirchheim, R.; Santos, G. N.; Manzione, R. L. [UNESP]; Zanetti, W. A.L. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
Water is considered a finite resource of great importance for the maintenance and subsistence of living beings. The continuous growth of water demands makes it necessary to develop management strategies for the water resources use and protection. The groundwater resources builds up a considerable portion of the fresh water overall availability and need to be consumed rationally and in a sustainable way. Therefore, groundwater monitoring networks, such as the Integrated Groundwater Monitoring Network (RIMAS), operated and maintained by the Geological Survey of Brazil (CPRM), are fundamental strategies. The present study deals with the application of the Menyanthes Software as a way of attributing statistical consistency to this data bank and to fill missing data in the observed series. The main rationale is to build up a model relating the rainfall background to the respective observed groundwater levels. The results obtained through this application provide standardized approaches for consistency in the RIMAS data bank, as well as tools for prognosis for the phreatic behavior amidst climatic events such as droughts, similar to what occurred between the years 2013 and 2015 in the southeast region of Brazil.
APLICAÇÃO DO MODELO PIRFICT NO BANCO DE DADOS DA RIMAS
Keywords: database; groundwater; Menyanthes Software; phreatic levels